Stress Management for Improved Living and Empowerment (SMILE): A Proposed Culturally Adapted Mindfulness-Based Program for Social Workers in the Philippines - Susmerano, Exxon (Indonesian Social Work Consortium (ISWC), 2025)
Abstract Social workers are essential in human service organizations as they play an important role in the implementation of programs and in addressing the needs of diverse populations. However, their well-being and performance can suffer due to the stress and challenges inherent in their work environments. This paper aims to address the urgent need to respond to social workers’ self-care needs by exploring the potential of a culturally adapted mindfulness-based intervention in addressing issues such as stress and depression among social workers in the Philippines. Through a review of relevant literature, this paper examined mindfulness-based intervention as an emerging self-care practice and approach to addressing work-related health issues. It proposed the development and assessment of the Stress Management for Improved Living and Empowerment (SMILE) program, which is a culturally tailored intervention designed to meet the unique needs of social workers. Pending successful evaluation of its feasibility, efficacy, and effectiveness, social welfare and human service organizations may implement the proposed intervention to promote self-care and empowerment among social workers.